Effect of the Egg Positioning in Shelves of Hatchery Incubators on Egg Weight Loss and Chick Yield - Kaewhom, Paitoon; Jaikaew, Nonglak; Phromnoi, Siriwadee; Poolsamran, Patcharawadee (Journal of Mahanakorn Veterinary Medicine, 2023)
Hatchery is the upstream of broiler production chain whose goal is to produce quality chicks. The temperature and humidity of the automatic controlled incubator must be consistent so as not to affect the embryo or chicks. This study was conducted to determine the effect of the egg positioning in shelves of incubators on egg weight loss and chick yield. The experimental design was completely randomized design (CRD). In this experiment, fertile eggs were randomly placed in different positions. The experiment was performed with 3 shelves position treatments which composed of group 1: shelve 1 (top floor), group 2: shelve 8 (middle floor), and group 3: shelve 15 (bottom floor). Fertile eggs were placed 5 replicate per group, 84 eggs per replicate. The fertile eggs were hatched in the hatchery incubators for 18 days and placed to born incubator for three days. Data were collected from weighing eggs prior to hatch, weighing eggs at 18 days of hatching and chicks weighed. The results showed that the egg positioning on shelves of incubators had no effect on egg weight loss, average chick weight and chick yield (P>0.05). From the above experimental results, it was shown that the automatic control of various factors in both the hatchery incubator and born incubator were consistent and did not affect chick production.